ALGORITHM FOR THE DIAGNOSTIC SEARCH OF STRUCTURAL AND FUNCTIONAL CHANGES IN THE MITRAL VALVE IN MITRAL INSUFFICIENCY OF ISCHEMIC GENESIS - Moroz, V.S.; Lazoryshіnets, V.V. (World of Medicine and Biology, 2024)
Established features of diagnostic data that influence the choice of surgical tactics for mitral valve correction. It was found that myocardial infarction was present in the anamnesis significantly more often in patients of the control group (p=0.04, χ2=4.09). More pronounced structural and anatomical changes of the mitral valve were established, which had statistical significance in patients of the control group, namely: prolapse of the leaflets: anterior (p=0.04; χ2=4.0) and both leaflets (p=0.02; χ2=5.24); frequency of calcinosis (р=0.006; χ2=7.58); calcinosis of the ring (p=0.01; χ2=5.58); reverse blood flow of a pronounced degree: (++)/(+++), (p=0.002; χ2=10.03) and very pronounced (+++)/(++++), (p=0.04; χ2=4.03) and severe mitral valve insufficiency (p=0.03; χ2=4.69).
Keywords: ischemic heart disease; mitral regurgitation; myocardial infarction; mitral insufficiency; operations on the mitral valve